Effectiveness of Nurse-Practitioner-Delivered Brief Motivational Intervention for Young Adult Alcohol and Drug Use in Primary Care in South Africa: A Randomized Clinical Trial. (4th June 2014) - Mertens, Jennifer R.; Ward, Catherine L.; Bresick, Graham F.; Broder, Tina; Weisner, Constance M.
Abstract : Aims: To assess the effectiveness of brief motivational intervention for alcohol and drug use in young adult primary care patients in a low-income population and country. Methods: A randomized controlled trial in a public-sector clinic in Delft, a township in the Western Cape, South Africa recruited 403 patients who were randomized to either single-session, nurse practitioner-delivered Brief Motivational Intervention plus referral list or usual care plus referral list, and followed up at 3 months. Results: Although rates of at-risk alcohol use and drug use did not differ by treatment arm at follow-up, patients assigned to the Brief Motivational Intervention had significantly reduced scores on ASSIST (Alcohol, Smoking and Substance Involvement Screening Test) for alcohol—the most prevalent substance. Conclusion: Brief Motivational Intervention may be effective at reducing at-risk alcohol use in the short term among low-income young adult primary care patients; additional research is needed to examine long-term outcomes.